Community Self-Empowerment in Optimizing Oral Cavity Movement through Elderly Oral Gymnastics - Endah Aryati Eko Ningtyas; Diyah Fatmasari; Lanny Sunarjo (Poltekkes Kemenkes Semarang, 2024)
The most common diseases in the elderly based on the 2018 Basic Health Research (Riskesdas) are stroke (77.7%), hypertension (41.62%), arthritis (34.18%), diabetes mellitus (12.32%), heart disease (8.5%), and dental and oral problems (87.6%). Basically, diseases suffered by the elderly are rarely with a single diagnosis, but almost always multi-diagnosis. One of the dental and oral health problems experienced by the elderly is Xerostomia (dry mouth). Xerostomia in the elderly can affect the quality of life, due to discomfort in the oral cavity, difficulty in speaking, bad breath and affecting dental and oral health. To overcome this problem, oral gymnastics is carried out for the elderly to maintain and improve the oral function of the elderly. This activity aims to improve the oral health of the elderly through proper diet and oral gymnastics that effectively stimulate saliva production and prevent problems such as dry mouth, gum infections, and tooth decay. Some of the steps taken are strengthening the knowledge and independence of the elderly through counseling, dental examinations, oral gymnastics and evaluation. The target of the activity is 21 elderly people in Padangsari Village. From the results of these activities, it can be concluded that this training provides benefits for the elderly in improving oral health. Through proper dietary patterns and oral exercises, it has been proven effective in maintaining and improving oral cavity function such as stimulating saliva production and preventing oral health problems that are often experienced by the elderly, such as dry mouth, gum infections, and tooth decay. Overall, this training program helps improve the quality of life of the elderly through a holistic and practical approach.Keywords: Community empowerment; optimization of oral cavity movements; oral exercises; elderly.